SOCIAL REFORMS TO REDUCE POVERTY: A COMPREHENSIVE APPROACH (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Abstract: This article explores the significance of social reforms in reducing poverty and promoting sustainable development. It highlights the key areas where social reforms can have a transformative impact on poverty reduction, including education, income redistribution, gender equality, healthcare, agriculture, and housing. The study emphasizes the importance of providing access to quality education and skill development opportunities to break the cycle of poverty. It also underscores the need for progressive taxation policies and income redistribution programs to ensure a more equitable distribution of resources. Gender equality and women's empowerment are identified as critical factors in poverty reduction. The study emphasizes the importance of accessible healthcare services and robust social protection programs in alleviating poverty. Additionally, sustainable agriculture practices, affordable housing, and inclusive urban development are recognized as vital components of social reforms to reduce poverty. The findings of this study provide valuable insights for policymakers and stakeholders in designing evidence-based strategies to combat poverty, foster economic empowerment, and create a more equitable society.